Integrative review about home care for children and adolescents (Research, Society and Development, 2020)
To describe the scientific evidence in the literature about home care for children and adolescents with special health care needs. Study of integrative literature review. The stages were respected: formulation of the protocol to guide the review and the research question; collection in databases; evaluation, analysis, interpretation, categorization of data and presentation of results and conclusions. The PECOS strategy for structuring data collection was followed: Population - children and adolescents; Exposure - special health needs; Comparison - not performed; Results - care received in home care; Study design - observational study of literature review. The international guide PRISMA guided the conduct of the study. Adaptation of the instrument was used to collect bibliographic information. Qualitative data were submitted to thematic content analysis. Home care for children and adolescents was addressed in 20 analyzed productions that mostly have level of evidence 2, according to an outline for meanings. The evidence showed that home care promotes dehospitalization and family ties, in addition to preventing new complications.Home care is able to offer expanded assistance to children and adolescents in a situation of illness, through humanized and comprehensive care.